Characterizing the effect of the rotational motion of a mobile receiver on the wireless signal reception in a non-line of sight indoor environment - Soriano, Referendo D.; Marciano, Joel Joseph S. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The characterization of wireless signals from the rotational motion of a mobile device as it affects the communication link is described in this work. These motions correspond to the rotation of the device around an axis and the on-axis motion commonly experienced during usage of ubiquitous mobile and other portable communication devices. The rotational motion around an axis resembles an arm or head azimuthal movements which exhibited random phase behavior. The on-axis motion is the pitch or roll movement modeled through varying polarization sensitivity of the embedded antenna of the device. The signals arriving at the mobile device are from the indoor non-line of sight environment using a theoretical two-dimensional Saleh and Valenzuela model or an empirical three-dimensional WINNER II channel model. The Probability Density Function (PDF) and Cumulative Distribution Function (CDF) supported by Kolmogorov Smirnov (KS) goodness of fit test characterized the magnitudes of the received signals after the rotational motion. Furthermore, the Second order statistical characteristic of the received signal namely Level Crossing Rate (LCR) and Average Fade Duration (AFD) of selected distributions from the KS test is explored to substantiate its outcome. The results show that in a two-dimensional channel model, the Nakagami distribution best describes the fading experienced from around an axis motion and the Weibull distribution for the on-axis rotation. In the case of three-dimensional Channel model, the Weibull distribution best characterizes the impairment caused by these newly considered range of motions, be it around an axis, on-axis or its combination, such as an up and down elevation swing. lt was also found that the varying polarization sensitivity from the on-axis rotational movements produces severe signal degradation. Hence, these findings on the characteristics of the wireless signals undergoing a range of rotational motions demonstrate a change in the usual perspective of fading in such environments and provide new insights on the modelling and prediction of radio signal propagation behavior. Using the best-fit distributions for the fading characteristics under rotational motion obtained in this study, the system performance in terms of the channel capacity can also be established. This work therefore also provides valuable groundwork for further research in channel modeling aimed at the improvement of wireless communication systems performance in mobile environments.
Thesis (Ph.D. Electrical and Electronics Engineering)--University of the Philippines Diliman
Keywords: Wireless communication systems; Mobile communication systems